Prevalence of hepatitis B and hepatitis C among blood donors in Baghdad, August 2007-December 2008. - Ali, Mariam K. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Hepatitis is a disease of the liver caused by the infectious and non-infectious agents.Patients &methods: A total of 600 blood donors attending blood bank at Baghdad city were included in this study , they were screened by Enzyme Immune sorbent Assay for detection of HBs Ag and anti-HCV ,that confirmed by recombinant immunoblot assay .the possible influence of the various factors on the prevalence was analyze too.Results: Form the total donors there were 37(6.2%)and 6(1.7%)positive for HBV &HCV respectively .peak prevalence for HBs Ag was noticed in age groups (20-29)years .Conclusion: Screening blood donors for both HBV and HCV is indispensable for safe blood transfusion. . In general, formulation of safe blood transfusion policy and implementation of standard screening protocols should be practiced.